Acrylamide in foods: from regulation and registered levels to chromatographic analysis, nutritional relevance, exposure, mitigation approaches, and health effects - Quesada Valverde, Mónica (2022)
Herein we explore the latest research on a chemical compound resulting from food processing and during the Maillard reaction: Acrylamide (ACR). ACR is formed during high-temperature cooking processes (i.e. >120 °C), such as frying, roasting, and baking. Considering the relevance of ACR in the food industry, first, we briefly explored the nature of ACR and its mechanisms of formation and current available legislative framework (with especial emphasis on baked goods and cereals, potato-based products, and coffee). Special attention was given to which foods are more likely to contain considerable amounts of ACR and the particulars of chromatographic methodologies involved in its testing (including extraction). Additionally, health effects caused by ACR were addressed that include an introduction to eukaryotic and prokaryotic ACR metabolism, biotransformation, and fate. Risk assessment, including a margin of exposure (MOE) and tolerance levels for ACR, was highlighted. Finally, we concluded our review with a section regarding methods and strategies available to reduce ACR in foods; this includes the role of asparagine (Asn), operation units available to industry, and the addition of natural products. ACR is still a relevant compound regarding food safety, and still, research is ongoing to develop methods for accurate surveillance and strategies for quenching its formation at the processing stage.